Speculative attacks in the exchange market with a band policy: A sequential game analysis - B. Gabriela Mundaca; Jon Strand (University of Oslo, Department of Economics, 1999)
We model the exchange rate market for a country that initially follows a band policy, as a four-stage sequential game of complete information, where a stochastic shock is realized in the last stage. Given a fixed cost of leaving the band, we show that three types of equilibria may exist, corresponding to different expectations by the public about the government retaining the band, (1) in all future states, (2) only in some future states, and (3) in none of the states. In case (2) a speculative attack occurs but is countered when the cost of countering it is not too high, leading to adverse shifts in fundamentals. We study the government's incentives to abandon or retain the band, and to abandon the band preemptively before public expectations are revealed. The standard Krugman and Obstfeld models are obtained as special cases, respectively when we have regime collapse as a unique equilibrium, and when there are multiple equilibria and the game always progresses to stage 4.
Keywords: F31; F33; 330; Currency crisis; multiple equilibria; sequential games; unemployment; Devisenmarkt; Devisenspekulation; Theorie